Understanding how mindfulness‑based interventions promote work‑life balance: a systematic review of randomized controlled trials - Trombeta, Gabriela; Barham, Elizabeth Joan; Bertho, Maria Alice Centanin (Universidade Federal de São Carlos, 2024)
The effects of mindfulness-based interventions (MBIs) on work-life balance (WLB) have been documented in previous experimental studies. However, work is needed to integrate the information that is emerging. In this study, we address this need by (a) conducting a systematic review of the effects of MBIs on WLB, and (b) proposing a logical model indicating how MBIs may contribute to WLB. The search was conducted using Psycnet, PubMed, Web of Science, Scopus, SciELO, and Redalyc e BVS Saúde databases, retrieving studies published up until July 2023. We selected studies involving randomized controlled trials in which the effects of an MBI on WLB and related outcomes were reported. Of the initial 575 texts, seven peer-reviewed articles were selected. Data analysis was conducted by examining key components of the MBIs, considering: (a) the intervention procedures, (b) effects on WLB, (c) explanations about behavioral change mechanisms, (d) study design limitations, and (e) suggestions for further research. Findings indicated that MBIs improved work-life balance outcomes (such as perceptions of WLB, satisfaction with WLB, and psychological detachment from work) and decreased work-family and work-life conflict. Follow-up studies showed that program effects were maintained. Higher retention rates were found for app-based interventions, interventions that had at least one in-person session, and programs in which participants could choose which exercises and when to practice. MBI mechanisms include self-regulation of attention, emotions, and behaviors to strengthen people’s psychological resources. Further research is needed to investigate the generalizability of the findings, to understand the range of people who can benefit from MBIs, and to clarify MBI outcomes involving adjustments in personal life involvements that may affect work behaviors.
Keywords: Boundary management; Emotion regulation; Work-life conflict; Workplace wellbeing